2022
DOI: 10.1001/jamahealthforum.2022.1632
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Unemployment-Related Health Insurance Coverage Changes in Medicaid Expansion vs Nonexpansion States During the COVID-19 Pandemic

Abstract: This cohort study compares changes in health insurance coverage for previously employed US adults in states with and without Medicaid expansion during the COVID-19 pandemic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…The association between insurance coverage and a past-year Papanicolaou test underscores the importance of ensuring financial access. The number of persons without insurance increased slightly between the spring and winter of 2020, but losses of employer-sponsored insurance were offset by enrollment in Medicaid between 2019 and 2020 . Continued increases in insurance coverage, whether through Medicaid expansions or Affordable Care Act Health Insurance Marketplace enrollment assistance programs, could be a factor in the receipt of cervical cancer screenings.…”
Section: Discussionmentioning
confidence: 99%
“…The association between insurance coverage and a past-year Papanicolaou test underscores the importance of ensuring financial access. The number of persons without insurance increased slightly between the spring and winter of 2020, but losses of employer-sponsored insurance were offset by enrollment in Medicaid between 2019 and 2020 . Continued increases in insurance coverage, whether through Medicaid expansions or Affordable Care Act Health Insurance Marketplace enrollment assistance programs, could be a factor in the receipt of cervical cancer screenings.…”
Section: Discussionmentioning
confidence: 99%
“…When states expanded Medicaid under the Affordable Care Act, the expanded guidelines allowed for more people to access the program during periods of joblessness (Benitez, Williams, et al, 2021a;Buchmueller et al, 2021). During the onset of the COVID-19 crisis, unemployment rose quickly from 3.5% to just under 15% between February and April 2020 (U.S. Bureau of Labor Statistics, 2021b) and Medicaid enrollments associated with job loss were more frequent in states that expanded Medicaid (Benitez, 2022;Benitez & Dubay, 2022;Jacobs & Moriya, 2023). In addition to eligibility guidelines, the fees that state Medicaid programs pay providers vary substantially across states, and how well Medicaid reimburses for provider services-or even whether Medicaid reimburses for selected services at all-could impact Medicaid's viability as a safety net program.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the COVID-19 pandemic, unemployment soared from 3.5% in February 2020 to 14.7% in April before falling to 6.7% in December . Research found that uninsurance rose among working-age adults due to falling employer-sponsored insurance (ESI) among newly unemployed workers that was only partially offset by Medicaid . We assessed racial and ethnic differences in uninsurance and coverage sources among working-age adults who worked in 2019 and 2020 (continuously employed) and who worked in 2019 but were unemployed in 2020 (newly unemployed).…”
Section: Introductionmentioning
confidence: 99%